Knowledge and Perception of Fluoridated Drinking Water Among Public in Kulaijaya, Johor - Noor Farhana Jalil; Shaharuddin Mohd Sham (STIKES Bhakti Husada Mulia Madiun, 2022)
Fluoride is an ionized form of the fluorine element which is can be found naturally in water bodies and fluoride is also being added into the drinking water supply to prevent and control tooth decay problems, especially among younger children. The purpose of this study is to determine the level of knowledge and perception about fluoride in drinking water among respondents. A cross-sectional study was conducted among 243 respondents who lived in Kulaijaya, Johor by convenience sampling method. They were required to answer an online questionnaire that consisted of three (3) sections, namelysocio-demographic characteristics, knowledge of fluoride in drinking water, and perception of fluoride in drinking water. Most (185 – 76.1%) of respondents were 18 to 64 years old and133 (54.7%) of them were female. Majority of them (153 – 63%)achieved tertiary education level and most (153 – 63%) lived for more than 10 years in the same location. The majority of respondents had poor knowledge level (164 - 67.5%) and a high perception level of fluoride in drinking water (83 - 34.2%). There was an association between educational level and knowledge level (x2=32.19, p-value = 0.000) while, there was no association found between socio-demographic factors (age, gender, educational level, and residential duration) and the public’s perception level of fluoride in drinking water.The local government is encouraged to collaborate with other agencies to implement more fluoridation programs to the public to raise awareness of water fluoridation as knowledge level have positive significance with the education exposure (p=0.000).